2021
DOI: 10.1016/j.tre.2021.102271
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic related supply chain studies: A systematic review

Abstract: The global spread of the novel coronavirus, also known as the COVID-19 pandemic, has had a devastating impact on supply chains. Since the pandemic started, scholars have been researching and publishing their studies on the various supply-chain-related issues raised by COVID-19. However, while the number of articles on this subject has been steadily increasing, due to the absence of any systematic literature reviews, it remains unclear what aspects of this disruption have already been studied and what aspects s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
645
4
25

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 691 publications
(685 citation statements)
references
References 154 publications
(308 reference statements)
11
645
4
25
Order By: Relevance
“…The impact of carbon damages on LPI is negative, which confirmed that countries restrict unstainable logistic activities and move towards clean and green logistics performance on a large scale. The greater needs to make strict environmental regulations and improve logistics green activities are desirable for achieving the healthcare sustainability agenda worldwide (Yu et al 2021 ; Safa et al 2021 ; Chowdhury et al 2021 ).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The impact of carbon damages on LPI is negative, which confirmed that countries restrict unstainable logistic activities and move towards clean and green logistics performance on a large scale. The greater needs to make strict environmental regulations and improve logistics green activities are desirable for achieving the healthcare sustainability agenda worldwide (Yu et al 2021 ; Safa et al 2021 ; Chowdhury et al 2021 ).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…In this line of thought, the literature dealing with the interplay between technologies approaches and COVID-19 shows a lack of a structured integration of key emerging technologies for COVID-19 control (Ivanov, 2020b ; S. Kumar et al, 2021 ; Queiroz, Ivanov et al, 2020 ). For example, despite the recent, rapid increase in the number of reviews (Chowdhury et al, 2021 ; Ranjbari et al, 2021 ; Surabhi & Anders, 2020 ), most of them are limited to fully explore the integration between emerging technologies and COVID-19 as a primary approach. In this regard, Surabhi and Anders ( 2020 ) presented a bibliometric analysis integrating business and management perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Ranjbari et al ( 2021 ) provided a systematic literature review with a focus on the issue of sustainability and COVID-19, and concluded by drawing an agenda considering sustainable development. In the supply chain field, Chowdhury et al ( 2021 ) made a systematic literature review and presented interesting research opportunities on this integration.…”
Section: Introductionmentioning
confidence: 99%
“…Considering this scenario, this paper addresses the problem of decentralized SC operational planning which is a common and practical decision-making 0.00 50,000.00 1,00,000.00 scenario in the real-world business environment. Moreover, the recent COVID-19 pandemic has forced many businesses to be decentralized to effectively operate their functions and thus has proved the necessity of proper SC planning (Chowdhury et al, 2021).…”
Section: Managerial Implicationsmentioning
confidence: 99%